2014
DOI: 10.1111/jocn.12700
|View full text |Cite
|
Sign up to set email alerts
|

Motivational interviewing to explore culturally and linguistically diverse people's comorbidity medication self‐efficacy

Abstract: Helping people to take their medications as prescribed is a key role for nurses to serve and protect the well-being of our increasingly multicultural communities. The use of interpreters in motivational interviewing requires careful planning and adequate resources for optimal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 30 publications
0
44
0
1
Order By: Relevance
“…Counseling methods could be employed during an inpatient stay to address low perceived health competence. Motivational interviewing, for example, is highly effective at supporting self-efficacy and has been used in a variety of settings in cardiovascular patients, ranging from diabetes care to obesity and smoking[48–52]. The effect of these interventions and others on perceived health competence warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Counseling methods could be employed during an inpatient stay to address low perceived health competence. Motivational interviewing, for example, is highly effective at supporting self-efficacy and has been used in a variety of settings in cardiovascular patients, ranging from diabetes care to obesity and smoking[48–52]. The effect of these interventions and others on perceived health competence warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior qualitative research has found that the patients often mention in focus groups: 1) the barriers they have to chronic illness medication self-efficacy and 2) that lack of knowledge of their medications can impede their confidence in managing a chronic medical condition such as diabetes. 20 Medication self-efficacy scales have been developed for both hypertension and glaucoma, but not for diabetes. 10 , 12 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…This finding supports the efficacy of hotline research determined in previous studies. A qualitative, exploratory study was conducted to study the perceptions of a group of culturally and linguistically diverse participants, with comorbidities such as CKD, to determine factors that affected their medication self-efficacy with the use of motivational interviewing using the telephone [19]. This study found that poor knowledge about drugs delayed the confidence necessary for optimal disease self-management [19].…”
Section: Discussionmentioning
confidence: 99%